Morphological Analysis of Composition in Explanatory Texts and Exposition in Indonesian Language Book Class VIII Revised Edition 2017 - Widayanti, Widayanti; Dzuhrisa, Mahanda; Anggara, Arya; Lisnawati, Iis (e-Journal of Linguistics; Vol 19 No 2 (2025): ejl-July, 2025)
The research entitled "Exploration of Compositional Wealth in Explanation and Exposition Texts in Indonesian Language Books for Class VIII Revised Edition 2017". The aim is to understand the form and meaning of composition in explanation and exposition texts in Indonesian Language Books for Class VIII Revised Edition 2017. The method applied is a qualitative descriptive method, with data obtained through analysis of explanation and exposition texts in Indonesian Language Books for Class VIII Revised Edition 2017. This study describes the categories of types and meanings of compositions found in explanation and exposition texts. The results obtained are two types of compositions based on their nature, namely endocentric and exocentric compositions, two types of compositions based on meaning, namely compositions that mean natural and figurative, and two types of compositions based on their composition, namely compositions whose compositions are complementary and sequential.